Evaluation of Network-Based Minimally Invasive VR Surgery Simulator. - Kazuyoshi TAGAWA; Hiromi T. TANAKA; Yoshimasa KURUMI; Masaru KOMORI; Shigehiro MORIKAWA (Studies in Health Technology & Informatics, 2016)
In this paper, we report a result of an experiment of a field trial of our network-based minimally invasive surgery simulator. In our previous paper, we proposed a network-based visuohaptic surgery training system for laparoscopic surgery. In addition, we proposed a volume-based haptic communication approach, which allows participants at remote sites on the network to simultaneously interact with the same target object in virtual environments presented by multi-level computer performance systems, by only exchanging a small set of manipulation parameters for the target object and additional packet for synchronization of status of binary tree and deformation of shared volume model. We implemented the approach into our network-based surgery simulator, and field trial of the simulator at three locations was performed.